2020
DOI: 10.1186/s12882-020-01822-9
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic calcification score as a predictor of clinical outcome in peritoneal dialysis patients: a prospective cohort study

Abstract: Background: Abdominal aortic calcification assessed by X-ray is recommended to evaluate vascular calcification in dialysis patients. It has been shown that abdominal aortic calcification score (AACS) is a predictor of adverse outcomes in hemodialysis patients, but evidence regarding its prognostic value in peritoneal dialysis (PD) patients is still insufficient. We aimed to examine the predictive role of AACS for major adverse cardiac and cerebrovascular events (MACCE) and mortality in PD patients. Methods: El… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…The first error is to ignore the PD treatment during the observation period, regardless of the treatment length (12, 18-22, 25, 26). The second is to censor the PD participants when shifting to HD, and such study design excludes those mortalities occurring after the change of renal replacement therapy modality, which is highly common (20,21,25). This also causes time-to-event analysis to show that the longer PD duration was associated with death because the incident patients with PD tend to shift to HD or have renal transplants rather than die on PD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The first error is to ignore the PD treatment during the observation period, regardless of the treatment length (12, 18-22, 25, 26). The second is to censor the PD participants when shifting to HD, and such study design excludes those mortalities occurring after the change of renal replacement therapy modality, which is highly common (20,21,25). This also causes time-to-event analysis to show that the longer PD duration was associated with death because the incident patients with PD tend to shift to HD or have renal transplants rather than die on PD.…”
Section: Discussionmentioning
confidence: 99%
“…This also causes time-to-event analysis to show that the longer PD duration was associated with death because the incident patients with PD tend to shift to HD or have renal transplants rather than die on PD. The third, and most important, error is that those studies cannot distinguish the effect on mortality of PD treatment from uremic exposure period (18)(19)(20)(21)(22)25). The longer PD duration before enrollment also means more extended exposure to uremia, which is associated with a higher mortality risk and needs further adjustment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another X-ray-based score was established by Kauppila et al [30] from a retrospective study involving 617 lateral lumbar radiographs performed on patients from the Framingham heart study. The Kauppila score, representing the abdominal aorta calcification score (AACS) [49], assesses vascular calcifications via lateral abdominal X-rays and was proven to be a simple, low cost assessment of subclinical vascular disease (Table 1). More recently, it was correlated with cardiovascular event prediction in a study involving 187 peritoneal dialysis patients, and was showed to improve risk stratification beyond the Framingham risk score in another study involving 184 hemodialysis patients [50].…”
Section: Radiology Techniquesmentioning
confidence: 99%